Magnetic element, magnetic memory, high frequency oscillator, and manufacturing method thereof

By using a crystalless wire layer containing tungsten and added element X in the magnetic memory device, the problems of incompatibility with the magnetic tunnel junction and poor thermal stability in the prior art are solved, and high magnetoresistance effect and good thermal stability are achieved.

JP2025056688APending Publication Date: 2025-04-08NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023212929
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-26
Filing Date
2023-12-18
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In existing magnetic memory devices, platinum material is incompatible with the magnetic tunnel crystal structure when used in the wire layer, and has poor magnetoresistance effect. At the same time, tungsten material has poor thermal stability in semiconductor processes.

Method used

A crystalless wire layer containing tungsten and additive element X is used to form a W-X alloy wire layer through cost plating or alternating plating to improve the spin Hall effect of the wire layer and is compatible with the magnetic tunnel junction.

Benefits of technology

The magnetoresistive effect is improved, and the thermal stability and performance of the memory device are enhanced by suppressing the influence of the wire layer on the crystal structure of the magnetic tunnel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025056688000001_ABST
    Figure 2025056688000001_ABST
Patent Text Reader

Abstract

To provide a magnetic element, a magnetic memory, a high frequency oscillator, and a manufacturing method thereof, which have a wiring layer made of a new material that has a high spin Hall effect and is highly compatible with a stacked body having a magnetic tunnel junction formed thereon.SOLUTION: The present disclosure provides a magnetic element 10, a magnetic memory, and a high-frequency oscillator, each of which includes a wiring layer 11 with an amorphous structure containing tungsten and an additive element X, and a stacked body 12 having a magnetic tunnel junction on the wiring layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a magnetic element, a magnetic memory, and a high-frequency oscillator. [Background technology]

[0002] Due to the explosive increase in the amount of information in recent years, attention has been focused on non-volatile memories that can retain information even when the power is turned off. One example of non-volatile memory is magnetic random access memory (MRAM), which uses the magnetization of a micro magnet as an information medium. As a representative example of a memory cell structure in MRAM, a spin transfer torque magnetoresistance element (STT-MRAM) has been developed in which a current is applied directly to a magnetic tunnel junction (MTJ), which is a recording element (see, for example, Non-Patent Document 1).

[0003] STT-MRAM requires a large current to be applied to a high-resistance MTJ to write information. Since the read and write paths are the same, there is a problem with the rewrite endurance. In addition, high-speed operation is difficult in order to prevent erroneous writing.

[0004] As a new MRAM structure that solves these problems, a spin-orbit torque magnetic memory element (SOT-MRAM) that writes information without applying a current directly to the MTJ has been proposed (see, for example, Patent Document 1 and Non-Patent Document 2). SOT-MRAM has the advantages of being more durable and capable of high-speed operation than STT-MRAM, and it is expected to be applied to cache memories in large-scale integrated circuits.

[0005] SOT-MRAM uses the spin Hall effect of the wiring layer connected to the MTJ when writing information. The spin Hall effect is a phenomenon in which, when a current is passed through the wiring layer, a flow of spin angular momentum (so-called spin current) occurs in a direction perpendicular to the current direction. Examples of spin Hall materials used in the wiring layer include platinum (Pt) and tungsten (W) (see, for example, Non-Patent Documents 3 to 5 and Patent Document 2).

Prior Art Documents

Patent Documents

[0006]

Patent Document 1

Patent Document 2

Non - Patent Documents

[0007]

Non - Patent Document 1

Non - Patent Document 2

Non - Patent Document 3

Non - Patent Document 4

Non - Patent Document 5

Summary of the Invention

Problems to be Solved by the Invention

[0008] Platinum, which is used as a material for the wiring layer, is poorly compatible with the crystal structure of the MTJ formed on it, resulting in a poor magnetoresistance effect. Tungsten, which is used as a material for the wiring layer, is considered a promising spin Hall material for the wiring layer because the β phase (so-called β-W) with an A15 structure has a high spin Hall effect and can maintain the magnetoresistance effect of the MTJ when SOT-MRAM is formed. However, β-W is in a metastable state, so there is a problem that it has poor heat treatment resistance in the semiconductor process of SOT-MRAM.

[0009] An object of the present invention is to provide a magnetic element, a magnetic memory, a high-frequency oscillator, and a method for manufacturing the same, which have a wiring layer made of a new material that has a high spin Hall effect and is highly compatible with a stack having a magnetic tunnel junction formed thereon. [Means for solving the problem]

[0010] According to one aspect of the present invention, there is provided a magnetic element, a magnetic memory, and a high-frequency oscillator, each of which includes a wiring layer having an amorphous structure containing tungsten and an additive element X, and a stack having a magnetic tunnel junction on the wiring layer.

[0011] According to the above aspect, the wiring layer having an amorphous structure containing tungsten and the additive element X has a high spin Hall effect, and since the wiring layer has an amorphous structure, the influence on the crystal structure of the laminate having a magnetic tunnel junction formed thereon is suppressed, thereby improving the compatibility between the wiring layer and the laminate, and a magnetic element, a magnetic memory, and a high-frequency oscillator having a high magnetoresistance effect can be provided.

[0012] According to another aspect of the present invention, there is provided a method for manufacturing a magnetic element, the method including the steps of forming a wiring layer having an amorphous structure, the wiring layer being formed using a material source including tungsten and an additive element X, and forming a stack having a magnetic tunnel junction on the wiring layer.

[0013] According to the above aspect, by forming a wiring layer having an amorphous structure containing tungsten and the additive element X, the spin Hall effect is enhanced, and since the wiring layer has an amorphous structure, the influence on the crystal structure of the laminate formed thereon is suppressed, thereby providing a manufacturing method for a magnetic element having a high magnetoresistance effect. [Brief description of the drawings]

[0014] [Figure 1] 1 is a schematic diagram of a magnetic element according to an embodiment; [Diagram 2] 5A to 5C are diagrams illustrating the operation of a magnetic element according to an embodiment. [Diagram 3] FIG. 13 is a schematic diagram of a magnetic element according to another embodiment. [Figure 4A] FIG. 13 is a schematic diagram of a magnetic element according to a modified example. [Figure 4B] FIG. 13 is a schematic configuration diagram of a magnetic element according to another modified example. [Diagram 5] 1 is a flowchart of a method for manufacturing a magnetic element according to an embodiment. [Figure 6A] FIG. 1 is a conceptual diagram of co-sputtering using a tungsten (W) sputter target and two sputter targets of an additive element (X). [Figure 6B] FIG. 1 is a conceptual diagram showing alternate sputtering using a tungsten (W) sputter target and two sputter targets of an additive element (X). [Figure 7] 4 is a diagram showing an example of a structure analysis by thin film X-ray diffraction of a wiring layer of the magnetic element according to the first embodiment. FIG. [Figure 8] 1 is a diagram showing an example of a structure analysis performed by a transmission electron microscope in Example 1. FIG. [Figure 9] FIG. 11 is a diagram showing the spin Hall effect of a magnetic element in a case where the wiring layer of the magnetic element in Example 2 is formed of W100-y(Ta82B18)y. [Figure 10A] FIG. 1 is a schematic diagram of a measurement circuit for spin current density. [Figure 10B] 1 is an example of a ferromagnetic resonance spectrum obtained by measuring the spin current density. [Figure 11]FIG. 13 is a diagram showing the spin Hall effect when the wiring layer of the magnetic element according to Example 3 is made of W90B10. [Figure 12] FIG. 13 is a diagram showing the spin Hall effect when the wiring layer of the magnetic element in Example 4 is made of W100-y(Mo80B20)y. [Figure 13] 13 is a magnetization curve of the magnetic element according to Example 5. [Figure 14] 13 is a cross-sectional transmission electron microscope image of Example 6 relating to a magnetic memory. [Figure 15] 13 is a magnetoresistance curve of Example 6. [Figure 16] 13 is a magnetoresistance curve of Example 7 related to a magnetic memory. [Figure 17] FIG. 13 is a diagram for determining characteristic values ​​of Examples 6 and 7. [Figure 18] FIG. 13 is a diagram showing characteristic values ​​of Examples 6 and 7. [Figure 19] FIG. 13 is a diagram showing the anomalous Hall effect of the magnetic memory according to Example 8. [Figure 20] FIG. 1 is a schematic diagram illustrating the configuration of a high-frequency oscillator according to an embodiment. [Figure 21] 13 is a frequency spectrum of an oscillation signal VOSC of the high-frequency oscillator according to Example 9. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Elements common to a number of drawings are given the same reference numerals, and detailed descriptions of those elements will be omitted. In the composition notation of the material of each layer, the numbers are expressed in atomic % (at%).

[0016] [Magnetic element] FIG. 1 is a schematic diagram of a magnetic element according to an embodiment. Referring to FIG. 1, the magnetic element 10 includes a wiring layer 11, a stack 12 having a magnetic tunnel junction on the wiring layer 11, and an electrode cap layer 13 on the stack 12. The stack 12 is formed by stacking a magnetization free layer 14, a tunnel barrier layer 15, and a reference layer 16 in this order from the wiring layer 11 side, forming a magnetic tunnel junction. When a pulse current is applied between the terminal 11a and the terminal 11b connected to the wiring layer 11, the magnetic element 10 generates a flow of spin angular momentum in a direction perpendicular to the current direction, that is, a spin orbit torque type spin current, which acts on the magnetization of the magnetization free layer 14 of the stack 12, and the magnetization direction of the magnetization free layer 14 is reversed depending on the polarity and magnetization direction of the spin current. This changes the magnetic resistance between the terminal 13a connected to the electrode cap layer 13 and the terminal 11a or the terminal 11b. The wiring layer 11 forms an amorphous alloy of tungsten (W) and an additive element (hereinafter also referred to as "additive element X"), so that the spin Hall effect is large and the magnetization of the magnetization free layer 14 can be reversed with low power.

[0017] The magnetization free layer 14 is formed on the wiring layer 11 and is made of a ferromagnetic material. The ferromagnetic material of the magnetization free layer 14 is selected from, for example, Fe-B, Co-Fe-B, Co-Ni-B, Fe-Ni-B, and the like. As for the composition, it is preferable that B is selected from the range of 10 at (atomic) % to 40 at %, in order to obtain an amorphous structure that promotes crystallization of the tunnel barrier layer 15. By using a Co-Fe-B film for the magnetization free layer 14, the magnetoresistance ratio of the magnetic element 10 can be made 100% or more. It is preferable that the thickness of the magnetization free layer 14 is set to 0.8 nm to 3 nm, in order to ensure the thermal stability of the magnetization free layer 14 and to allow writing control.

[0018] When no external magnetic field is applied, the magnetization direction of the magnetization free layer 14 may be parallel to the film surface, i.e., in-plane, or perpendicular to the film surface, i.e., perpendicular to the film surface. The magnetization direction of the magnetization free layer 14 is influenced by the magnetic field from the magnetization of the magnetization fixed layer of the reference layer 16, exchange interaction, or the in-plane shape anisotropy of the magnetization free layer 14.

[0019] The tunnel barrier layer 15 is formed on the magnetization free layer 14 and is made of an insulating material, for example, MgO. The thickness of the tunnel barrier layer 15 is preferably set to 0.8 nm to 2.5 nm in order to obtain a high magnetoresistance ratio and a high output.

[0020] The reference layer 16 is formed on the tunnel barrier layer 15 and is made of a ferromagnetic material. The reference layer 16 is a magnetization fixed layer in which the direction of magnetization is almost fixed. The ferromagnetic material of the reference layer 16 may be CoFe, Co-Fe-B, Fe-B, a CoPt laminated film, a CoPd laminated film, or the like. The thickness of the reference layer 16 is preferably set to 3 nm to 10 nm in order to ensure high thermal stability.

[0021] The electrode cap layer 13 is formed on the reference layer 16 from a conductive material, and is made of, for example, a laminate of a Ta layer and a Ru layer.

[0022] The wiring layer 11 is made of an amorphous alloy of tungsten (W) and an additive element X (hereinafter, also referred to as a "WX alloy"). The additive element X preferably contains at least one element of boron (B), phosphorus (P) and carbon (C) (hereinafter, also referred to as an "element NM"), in that the wiring layer 11 can maintain an amorphous structure. The additive element X preferably contains at least one metal element of tantalum (Ta) and molybdenum (Mo) (hereinafter, referred to as a "metal element M") in addition to at least one element of boron (B), phosphorus (P) and carbon (C) (element NM), in that the spin Hall angle is high. The spin Hall angle is the ratio of the spin current density generated to the unit current density of the pulse current passed between the terminals 11a and 11b of the wiring layer 11 (i.e., the current value relative to the cross-sectional area of ​​the wiring layer 11 perpendicular to the flow of the pulse current). The spin current density is the spin angular momentum with respect to the surface area in the stacking direction of the wiring layer 11, and can be measured by, for example, spin torque ferromagnetic resonance. The thickness of the wiring layer 11 is preferably set to 3 nm to 20 nm, in order to maximize the spin current injected into the magnetization free layer 14.

[0023] The content of the additive element X in the wiring layer 11 is preferably 5 at % or more, more preferably 10 at % or more, and 50 at % or less, more preferably 40 at % or less, in order to realize a high spin Hall effect against heat treatment. The content of the additive element X in the wiring layer 11 may have a structure in which the content of the additive element X gradually changes from the bottom of the wiring layer 11 to the top, i.e., toward the magnetization free layer 14, within this preferred range, that is, a composition gradient structure, and a structure in which the content of the additive element X gradually decreases from the bottom of the wiring layer 11 to the top is more preferred.

[0024] When the wiring layer 11 contains tungsten (W) and the element NM but does not contain the metal element M, the content of the element NM is preferably 5 at% or more and 50 at% or less, in terms of the ability of the wiring layer 11 to maintain an amorphous structure. When the wiring layer 11 contains tungsten (W) and the element NM and the metal element M, the content of the element NM in the additive element X is preferably 10 at% or more, more preferably 15 at% or more, and 50 at% or less, more preferably 45 at% or less, in terms of the ability to achieve a high spin-Hall angle. In addition, in the WX alloy film, the content of the element NM is preferably 5 at% or more, in terms of the ability to maintain an amorphous structure against heat treatment.

[0025] FIG. 2 is an explanatory diagram of the operation of a magnetic element according to an embodiment. This is an example in which the magnetic element is used as a magnetic memory. Referring to FIG. 2, the magnetic element 10 has a wiring layer 11, a cylindrical laminate 12 and an electrode cap layer 13 on the wiring layer 11, and the wiring layer 11 has two terminals 11a and 11b at both ends in the direction in which a pulse current flows, and the electrode cap layer 13 has a terminal 13a. When reversing the magnetization direction of the magnetization free layer 14 of the laminate 12 (for example, when writing information), a current pulse is passed from one of the terminals 11a and 11b to the other. A spin current that flows perpendicular to the current flow is generated from the current pulse flowing through the wiring layer 11, and flows upward through the laminate 12. The spin current acts on the magnetization of the magnetization free layer 14 to reverse the direction of magnetization. In this way, information is written into the magnetization free layer 14 of the magnetic memory 10, and when the magnetization direction of the magnetization free layer 14 is the same as the magnetization direction of the reference layer 16 (i.e., parallel), the stack 12 exhibits the lower of the two magnetoresistance values, and when the magnetization direction is different (i.e., anti-parallel), the stack 12 exhibits the higher of the two magnetoresistance values.

[0026] When reading information, a pulse current is applied from the terminal 13a and passes through the electrode cap layer 13 and the stack 12 to reach, for example, the terminal 11b. Information on the magnetization direction of the magnetization free layer 14 is obtained based on the magnitude of the voltage drop between the terminal 13a and the terminal 11b. The operation during reading is the same as that of a conventional spin transfer torque magnetic memory (STT-MRAM).

[0027] FIG. 3 is a schematic diagram of a magnetic element according to another embodiment. Referring to FIG. 3 together with FIG. 1, the magnetic element 20 includes a wiring layer 11, a stacked body 22 having a magnetic tunnel junction on the wiring layer 11, and an electrode cap layer 13 on the stacked body 22. The stacked body 22 is formed by stacking a magnetization free layer 14, a tunnel barrier layer 15, and a reference layer 26 in this order from the wiring layer 11 side, and forms a magnetic tunnel junction. The reference layer 26 is formed by stacking a first ferromagnetic layer 31, a nonmagnetic spacer layer 32, a second ferromagnetic layer 33, and an antiferromagnetic layer 34 in this order from the tunnel barrier layer 15 side. The magnetic element 20 is the same as the magnetic element 10 shown in FIG. 1, except that the configuration of the reference layer 26 is different.

[0028] The reference layer 26 has a synthetic ferrimagnetic (SAF) structure in which a first ferromagnetic layer 31 and a second ferromagnetic layer 33 are antiferromagnetically coupled with a nonmagnetic spacer layer 32 sandwiched therebetween. The first ferromagnetic layer 31 is antiferromagnetically coupled with the second ferromagnetic layer 33, so that the magnetization direction of the first ferromagnetic layer 31 is almost (substantially) fixed. Furthermore, the second ferromagnetic layer 33 is exchange-coupled with an antiferromagnetic layer 34, which applies an exchange bias magnetic field to the second ferromagnetic layer 33, so that the magnetization direction of the second ferromagnetic layer 33 is almost fixed, and as a result, the magnetization direction of the first ferromagnetic layer 31 is fixed. Note that the antiferromagnetic layer 34 is not essential.

[0029] The first ferromagnetic layer 31 and the second ferromagnetic layer 33 are set to a thickness of, for example, 1 nm to 5 nm, and may be made of a ferromagnetic material such as a Co-Fe, Co-Fe-B, Fe-B, Co, or CoPt laminated film.

[0030] The nonmagnetic spacer layer 32 has a thickness set to, for example, 0.2 nm to 2 nm, and may be made of a nonmagnetic material such as V, Cr, Cu, Mo, Ru, Rh, Ta, W, Re, or Ir.

[0031] The antiferromagnetic layer 34 has a thickness set to, for example, 5 nm to 10 nm, and may be made of an antiferromagnetic material such as Ir--Mn or Pt--Mn.

[0032] Figures 4A and 4B are schematic configuration diagrams of the magnetic elements of the modified examples of Figures 1 and 3, respectively. With reference to Figures 4A and 4B, the magnetic elements 40 and 50 have the same configuration as the magnetic element 10 shown in Figure 1 and the magnetic element 20 shown in Figure 3, except that a thin film 41 containing a material other than the elements constituting the wiring layer 11 is formed between the wiring layer 11 and the magnetization free layer 14.

[0033] It is preferable that the thin film 41 contains at least one of the metal elements Ti, V, Cr, Co-O, Fe-O, Ni-O, Cu, Zr, Nb, Pd, Hf, Ir, Pt, and Au or an oxide thereof, in order to improve the magnetic properties of the magnetization free layer 14, for example, to reduce the anisotropy field, suppress the magnetic damping constant, and obtain a high spin Hall angle.

[0034] In the magnetic elements 10, 20, 40, and 50, when a pulse current is applied between the terminals 11a and 11b of the wiring layer 11, a flow of spin angular momentum (i.e., spin current) occurs in a direction perpendicular to the current direction, which acts on the magnetization of the magnetization free layer 14 of the stack 12 and generates a torque that rotates the magnetization. A so-called spin orbit torque type torque is generated. This torque rotates the magnetization of the magnetization free layer 14 and settles in an energetically stable direction. When the magnetization of the magnetization free layer 14 is parallel to the film surface, that is, the in-plane direction is energetically stable, when a pulse current flows through the wiring layer 11, depending on the polarity of the pulse current and the direction of magnetization, the magnetization may rotate 180 degrees (i.e., reverse) and point to another in-plane direction, or may remain in the same in-plane direction. The wiring layer 11 of this embodiment forms an amorphous alloy of tungsten (W) and the additive element X, and therefore has a large spin Hall effect, making it possible to reverse the magnetization of the magnetization free layer 14 with low power.

[0035] In the magnetic elements 10, 20, 40, and 50, even when the magnetization of the magnetization free layer 14 is perpendicular to the film surface, i.e., the direction perpendicular to the film surface is energetically stable, a spin-orbit torque acts on the magnetization of the magnetization free layer 14, and the magnetization direction is reversed. An example of the configuration of the magnetic element 10 in which the magnetization of the magnetization free layer 14 is perpendicular to the film surface is as follows. The thickness of each layer is within the preferred range. The configuration example is described in the order of stacking on the substrate.

[0036] {Configuration example 1} Wiring layer 11: WX alloy, thickness 3 to 20 nm Free magnetic layer 14: Co-Fe-B, thickness 1-2 nm Tunnel barrier layer 15: MgO, thickness 0.8 to 2.0 nm The reference layer 26 is a laminate of: First ferromagnetic layer 31: Co-Fe-B, thickness 1-2 nm Non-magnetic spacer layer 32: W, thickness 0.15 nm Second ferromagnetic layer 33: Co / Pt multilayer film, thickness 2-5 nm Non-magnetic spacer layer: Ru or Ir, thickness 0.15 nm Third ferromagnetic layer: Co / Pt multilayer, thickness 2-5 nm Electrode cap layer 13: Ru, Ta or Pt, thickness 3 to 20 nm

[0037] {Configuration example 2} Wiring layer 11: WX alloy, thickness 3 to 20 nm Thin film: Hf, Mo or Ti, thickness 0.5-1.0 nm Free magnetic layer 14: Co-Fe-B, thickness 1-2 nm Tunnel barrier layer 15: MgO, thickness 0.8 to 2.0 nm The reference layer 26 and the electrode cap layer 13 are the same as those in the first configuration example. The WX alloy of the wiring layer 11 may be a WX alloy film, which will be described later in the manufacturing method, or a W / X multilayer film.

[0038] In the above configuration examples 1 and 2, the exchange interaction of the Co / Pt multilayer film of the reference layer 26 causes the magnetization of the first ferromagnetic layer 31 to be perpendicular to the film surface, which in turn causes the magnetization of the magnetization free layer 14 to be perpendicular to the film surface.

[0039] In the above configuration examples 1 and 2, the magnetization free layer 14 is Co-Fe-B, but is not limited thereto and may be Fe-B, for example. In the magnetic element 10, when the magnetization of the magnetization free layer 14 is perpendicular to the film surface, that is, the surface perpendicular direction (z direction or -z direction) is energetically stable, a bias magnetic field may be applied to the magnetization free layer 14 in the direction (x direction) of the pulse current flowing through the wiring layer 11 or the opposite direction (-x direction). This tilts the magnetization of the magnetization free layer 14 from the z direction or -z direction to the x direction or -x direction by a certain angle (for example, 5°). This causes the magnetization of the magnetization free layer 14 to be reversed from one direction (for example, z direction) perpendicular to the surface to the opposite direction (for example, -z direction) or the opposite case depending on the direction of the pulse current flowing through the wiring layer 11.

[0040] [Method of manufacturing magnetic elements] 5 is a flowchart of a method for manufacturing a magnetic element according to an embodiment. The method for manufacturing a magnetic element according to an embodiment will be described with reference to FIG. 5 together with FIG.

[0041] First, a substrate is prepared (S100). The substrate is made of a non-magnetic material, and is, for example, a silicon substrate, a silicon substrate with a thermal oxide film, or a gallium arsenide substrate, but is not particularly limited thereto.

[0042] Next, the wiring layer 11 is formed on the substrate (S110). Specifically, a material source containing tungsten and an additive element X, for example, a sputtering target containing tungsten W and an additive element X, is prepared. The wiring layer 11 is formed by a sputtering method or the like (the wiring layer 11 thus formed is also referred to as a "WX alloy film"). The additive element X preferably contains at least one element of boron (B), phosphorus (P) and carbon (C) (hereinafter also referred to as "element NM"), in that the wiring layer 11 can maintain an amorphous structure. The additive element X preferably contains at least one metal element of Ta and Mo in addition to at least one element (element NM) of boron (B), phosphorus (P) and carbon (C), in that the spin Hall angle is high. The material source containing tungsten and the additive element X preferably contains the additive element X in an amount of 5 at% or more, more preferably 10 at% or more, and 50 at% or less, more preferably 40 at% or less, in that the spin Hall angle is high. When the material source contains tungsten (W) and the element NM but does not contain the metal element M, the content of the element NM is preferably 5 at% or more and 50 at% or less in order to maintain the amorphous structure of the wiring layer 11. When the material source contains tungsten (W) and the element NM and the metal element M, the content of the element NM in the additive element X is preferably 10 at% or more, more preferably 15 at% or more, and 50 at% or less, more preferably 45 at% or less in order to maintain the amorphous structure of the formed magnetic element against heat treatment. Also, in the WX alloy film, the content of the element NM is preferably 5 at% or more in order to maintain the amorphous structure against heat treatment.

[0043] When a sputtering method is used to form the wiring layer 11, it is preferable that the substrate temperature is 1° C. to 50° C. in order to form an amorphous structure. For example, an inert gas is used as the atmospheric gas, and krypton is preferable. It is preferable that the thickness of the wiring layer 11 is set to 3 nm to 20 nm in order to obtain a high spin Hall angle.

[0044] In S110, as an alternative method for forming the wiring layer 11, power may be supplied to two sputtering targets, one of which is a tungsten W sputtering target and the other of which is an additive element X, and the wiring layer 11 may be formed by simultaneously scattering sputter particles from the two sputtering targets (so-called co-sputtering or co-sputtering). This allows the wiring layer 11 to be formed of an alloy having an amorphous structure containing tungsten and the additive element X. Alternatively, the wiring layer 11 may be formed of an alloy having an amorphous structure containing tungsten and the additive element X by alternately stacking the sputter particles of tungsten and the sputter particles of the additive element X.

[0045] 6A and 6B are conceptual diagrams for explaining an alternative method for forming the wiring layer 11. Fig. 6A is a conceptual diagram of co-sputtering using a sputter target of tungsten W and two sputter targets of an additive element X. Fig. 6B is a conceptual diagram of alternate sputtering using a sputter target of tungsten W and two sputter targets of an additive element X.

[0046] 6A, a WX alloy film is formed by supplying power to two sputtering targets, one for tungsten and the other for additive element X, and depositing the tungsten sputter particles and the additive element X sputter particles simultaneously (co-sputtering). The composition ratio of the WX alloy film is controlled by adjusting the sputtering power supplied to each sputtering target.

[0047] Referring to FIG. 6B, tungsten layers and additive element X layers are alternately stacked n times (the wiring layer 11 thus formed is also called a "W / X multilayer film"). The thickness of each of the tungsten layer and the additive element X layer is preferably 1.0 nm or less in order to maintain an amorphous structure against heat treatment. The ratio of the thickness of one additive element X layer to the sum of the thickness tw of one tungsten layer and the thickness tx of one additive element X layer (i.e., tx / (tw+tx)) is preferably 0.10 or more and 0.50 or less. The number of repeated stacking times n is preferably 3 or more and 20 or less. Note that in FIG. 6, the boundary between the tungsten layer and the additive element X layer is clearly drawn, but since the thickness of each of the tungsten layer and the additive element layer in the wiring layer 11 after stacking is very thin and has an amorphous structure, it is difficult to measure the thicknesses tx and tx of each layer. The thicknesses tw and tx of each layer are preferably controlled by determining the deposition rate using a film thickness monitor and controlling the deposition time.

[0048] 5, next, stacked bodies 12, 22 having a magnetic tunnel junction are formed on the wiring layer 11 (S120). Specifically, for example, by sputtering, in the example of the magnetic element 10 shown in FIG. 1, the magnetization free layer 14, the tunnel barrier layer 15, and the reference layer 16 are deposited in this order on the wiring layer 11, and in the example of the magnetic element 20 shown in FIG. 3, the magnetization free layer 14, the tunnel barrier layer 15, the first ferromagnetic layer 31, the nonmagnetic spacer layer 32, the second ferromagnetic layer 33, and the antiferromagnetic layer 34 of the reference layer 26 are deposited in this order on the wiring layer 11.

[0049] Next, an electrode cap layer is formed (S130). Specifically, a laminate of a Ta layer and a Ru layer is formed on the laminates 12 and 22 by, for example, sputtering.

[0050] Next, the magnetic element formed in S130 may be heat-treated (S140). Specifically, the heat treatment temperature is preferably, for example, 300°C to 420°C, in that the magnetic properties of the ferromagnetic layers, such as the magnetization free layer 14 and the reference layer 16, are improved and crystallization of the wiring layer 11 does not occur. The heat treatment time is preferably 0.5 hours to 3 hours. The heat treatment may be performed continuously after the magnetic element formed in the steps up to S130, or may be performed after exposing it to the air. In this manner, the magnetic element is formed.

[0051] <Example 1> 7 is a diagram showing an example of a structure analysis by thin film X-ray diffraction of the wiring layer of Example 1 of the magnetic element, and is an example using the θ-2θ method of thin film X-ray diffraction. The chart of the wiring layer of Example 1 is shown by a solid line, and the chart of the wiring layer of the comparative example is shown by a dashed line. In Example 1, Ta 80 B 20 layer (thickness 1 nm), and the wiring layer 11 is W 67.9 (Ta 82 B 18 ) 32.1 (thickness 10 nm), Co-Fe-B (thickness 3 nm) as the magnetization free layer 14, MgO (thickness about 2 nm) as the tunnel barrier layer 15, and Ta-O layer (thickness 2 nm) as the electrode cap layer 13 were laminated in this order. 80 B 20 The wiring layer was formed by co-sputtering using a sputtering target of tungsten W and Ta 82 B 18 The composition ratio (67.9:32.1) was controlled by the sputtering power of each sputtering target. The formation of the reference layer 16 was omitted because it does not affect the structure of the wiring layer. Comparative Example 1 is the same as Example 1, except that the wiring layer is a metastable β-phase (A15 structure) tungsten layer (crystalline) (thickness 5 nm) formed using a tungsten sputtering target.

[0052] 7, the wiring layer of Example 1 showed a broad halo pattern without a diffraction peak in the diffraction pattern over the 2θ range of 35° to 45°. This shows that the wiring layer of Example 1 is in a non-crystalline (amorphous) state. On the other hand, the wiring layer of Comparative Example 1 shows a diffraction peak at 2θ of around 41°, showing that it is crystalline. The X-ray diffraction device used was Malvern Panalytical, model: X'Pert Pro. Cu-Kα rays were used as X-rays.

[0053] Fig. 8 shows an example of structural analysis by a transmission electron microscope in Example 1, which is an example using a transmission electron microscope (TEM). Fig. 8(a) is a cross-sectional TEM image of Example 1. Fig. 8(b) and (c) are nanobeam diffraction images of region 1 and region 2 of the wiring layer shown in (a), respectively.

[0054] Referring to FIG. 8(a), it can be seen that the wiring layer of Example 1 does not have any crystal planes, and does not contain any nanocrystals in the cross-sectional TEM image. Referring to FIGS. 8(b) and (c), no clear disk-shaped diffraction images were observed in the nanobeam diffraction images of region 1 and region 2 in the wiring layer of Example 1. From these findings, it can be seen that the wiring layer of Example 1 is in an amorphous state. The transmission electron microscope used was a NEOARM atomic resolution analytical electron microscope, model JEM-ARM200F, manufactured by JEOL Ltd. The nanobeam diffraction conditions were a camera length of 0.8 m, an acceleration voltage of 200 kV, and a beam diameter on the sample of about 5 nm.

[0055] <Example 2> In Example 2, Ta 82 B 18 layer (thickness 1 nm), and the wiring layer 11 is W 100-y (Ta 82 B 18 ) y(thickness 5 nm) (y=16, 22.9, 32.1, 42.4, 50.1, 65.6, 77.9, 100), Co-Fe-B (thickness 3 nm) as the magnetization free layer 14, MgO (thickness about 2 nm) as the tunnel barrier layer 15, and Ta-O layer (thickness 2 nm) as the electrode cap layer 13 were laminated in this order. The fixed magnetization layer was omitted because the purpose was to measure the spin Hall effect. The wiring layer 11 was formed by sputtering a tungsten W target and Ta 80 B 20 The wiring layer 11 was formed by co-sputtering using a sputtering target of tungsten and Ta 82 B 18 The composition ratio (100-y:y) was controlled by the sputtering power. In the magnetic element of Comparative Example 2, the wiring layer 11 was a β-phase tungsten layer (crystalline) (thickness 5 nm), and the other layers were the same as those of Example 2.

[0056] FIG. 9 shows a wiring layer of the magnetic element according to the second embodiment. 100-y (Ta 82 B 18 ) y 9(a) is a graph showing the spin Hall effect when the wiring layer is formed by the composition of the wiring layer, and the spin current density ξ SHE 9(b) is a graph showing the absolute value of the spin current density ξ per unit electric field in the wiring layer versus the composition of the wiring layer. SHE 1 is a diagram showing the absolute value of the spin current density ξ SHE The larger the absolute value of , the larger the spin Hall effect is, and the smaller the current or electric field required for spin injection into the free magnetization layer is. In the figure, black circles (●) and black triangles (▲) represent Example 2, and white circles (○) and white triangles (△) represent Comparative Example 2.

[0057] Referring to FIG. 9(a), in Example 2, when y is 16 to 60 at %, the spin current density ξ SHE It can be seen that the absolute value of is about 20% or more, and is higher than that of Comparative Example 2 when y is 16 to 40 at %.

[0058] Referring to FIG. 9B, in Example 2, when y is 16 to 60 at %, the spin current density ξSHE The absolute value of is 1(10 3 Ω -1 cm -1 ) and it can be seen that the smaller y is, that is, the more tungsten is contained, the higher the value becomes. It can be seen that Example 2 is higher than Comparative Example 2 when y is 16 to 40 at %.

[0059] Spin current density ξ SHE was measured by a method using magnetic damping modulation using spin torque ferromagnetic resonance (see, for example, L. Liu et.al, Phys. Rev. Lett. 106.036601 (2011)). SHE In this study, an external magnetic field was applied at a specific angle to the film surface of the magnetization free layer, causing the magnetization of the magnetization free layer to undergo precession motion due to ferromagnetic resonance, and a direct current was passed through the wiring layer 11 to measure the spin current flowing from the wiring layer 11 to the magnetization free layer 14 from the degree of modulation of the resonance linewidth caused by the spin-orbit torque acting on the magnetization. More specifically, the method is as follows.

[0060] 10A is a schematic diagram of a measurement circuit for the spin current density. Referring to FIG. 10A, the measurement circuit supplies a direct current I DC (Keysight Model: B2902A) and microwave current I RF (Microwave generator Keysight Corporation Model: 5173B EXG-Series) is applied. Microwave current I RF The ferromagnetic resonance of the free magnetic layer is induced by the voltage V FMR Detect by measuring the voltage V FMR In order to improve the measurement accuracy of the microwave current I RF The voltage was modulated using a lock-in amplifier (Stanford Research Corporation, Model SR830 DSP Digital Lock-in Amplifier).

[0061] FIG. 10B is an example of a ferromagnetic resonance spectrum obtained by measuring the spin current density. The horizontal axis represents the external magnetic field μH applied in the in-plane direction (μ is the magnetic permeability in a vacuum), and the vertical axis represents the voltage V FMR The black circle (●) indicates the case where a direct current of +2 mA is passed through the wiring layer, and the white circle (◯) indicates the case where a direct current of -2 mA is passed through the wiring layer.

[0062] Referring to FIG. 10B, the ferromagnetic resonance of the magnetization free layer is regulated by a rectified voltage V FMR is obtained, and V FMR The resonance linewidth W was calculated from the spectral shape of the AC current. DC flows, and a direct current I DC Change in resonance linewidth according to

number

number

number

number

[0063] <Example 3> In Example 3, Ta 82 B 18 layer (thickness 1 nm), and the wiring layer 11 is W 90 B 10 A layer (thickness 5 nm) was laminated as the free magnetization layer 14 made of Co-Fe-B (thickness 3 nm), a layer (thickness approx. 2 nm) was laminated as the tunnel barrier layer 15, and a layer (thickness 2 nm) of Ta-O was laminated as the electrode cap layer 13 in this order, and then the layer was heat-treated at 350° C. for 1 hour. The fixed magnetization layer was omitted because the purpose of the measurement was to measure the spin Hall effect. The wiring layer 11 was made of W. 90 B 10 The film was formed by sputtering using a sputtering target of 1000 g / cm2.

[0064] FIG. 11 shows a wiring layer of the magnetic element according to the third embodiment. 90 B 10 11(a) shows the spin Hall effect when the current density ξ SHE FIG. 11(b) shows the absolute value of the spin current density ξ per unit electric field in the wiring layer. SHE 11 is a diagram showing the absolute values ​​of .times. ...

[0065] Referring to FIG. 11(a), in Example 3, the spin current density ξ SHE It can be seen that the absolute value of is about 31%, which is a high value equivalent to that of Comparative Example 2. Referring to FIG. 11(b), in Example 3, the spin current density ξ SHE The absolute value of is 1.5(10 3 Ω -1 cm -1 ), which is as high as that of Comparative Example 2. From these, it can be seen that Example 3 has excellent heat resistance to heat treatment and can obtain a high spin Hall angle by forming the wiring layer from a material in which B is added to W.

[0066] <Example 4> FIG. 12 shows a wiring layer of the magnetic element according to the fourth embodiment. 100-y (Mo 80 B 20 )y 12(a) is a graph showing the spin Hall effect when the wiring layer is formed by the above formula: SHE FIG. 12(b) is a graph showing the absolute value of the spin current density ξ per unit electric field in the wiring layer versus the composition of the wiring layer. SHE FIG.

[0067] In Example 4, a W wiring layer 11 was formed on a substrate for measuring the spin Hall effect. 100-y (Mo 80 B 20 ) y (thickness 8 nm) (y=10, 14, 20, 25, 30, 35), Co-Fe-B (thickness 3 nm) as the magnetization free layer 14, MgO (thickness about 2 nm) as the tunnel barrier layer 15, and Ta-O layer (thickness 2 nm) as the electrode cap layer 13 were laminated in this order. The fixed magnetization layer was omitted. The wiring layer 11 was formed by sputtering a tungsten W target and a Mo 80 B 20 The wiring layer 11 was laminated by co-sputtering a sputtering target of tungsten and Mo. 80 B 20 The composition ratio (100-y:y) was controlled by the sputtering power of each sputtering target.

[0068] Referring to FIG. 12(a), in Example 4, when y is 10 to 35 at %, the spin current density ξ SHE It can be seen that the absolute value of is approximately 30% or more.

[0069] Referring to FIG. 12(b), in Example 4, when y is 10 to 35 at %, the spin current density ξ SHE The absolute value of is 1(10 3 Ω -1 cm -1 ) and it can be seen that the smaller y is, i.e., the more tungsten there is, the higher the tendency is.

[0070] <Example 5> The fifth embodiment is an example of a magnetic element in which the magnetization of the magnetization free layer is perpendicular to the film surface. 67.9 (Ta 82 B 18 ) 32.1 (thickness 8 nm), magnetic free layer 14: Fe 80 B 20 (thickness 1 nm), tunnel barrier layer 15: MgO (thickness about 1.5 nm), first ferromagnetic layer 31: (Fe 91 Co9) 80 B 20 (thickness 1 nm), non-magnetic spacer layer 32: W (thickness 0.2 nm), second ferromagnetic layer 33: multilayer film of Co (thickness 0.4 nm) / Pt (thickness 1 nm) and Co (thickness 0.4 nm) / Pt (thickness 0.6 nm) (repeated lamination number 3) and Co (thickness 0.3 nm), non-magnetic spacer layer: Ru (thickness 0.47 nm), third ferromagnetic layer: multilayer film of Co (thickness 0.4 nm) / Pt (thickness 0.6 nm) and Co (thickness 0.24 nm) / Pt (thickness 0.36 nm) (repeated lamination number 8), electrode cap layer 13: Pt (thickness 3 nm) / Ru (thickness 5 nm) were laminated in this order. The wiring layer 11 was formed by sputtering a tungsten W target and Ta 80 B 20 The sputtering targets were co-sputtered to obtain the desired composition ratio.

[0071] FIG. 13 shows the magnetization curve of the magnetic element of Example 5. The magnetization curve was obtained by applying a magnetic field perpendicular to the film surface of Example 5 and sweeping between −0.4 T and 0.4 T using a vibrating sample magnetometer (VSM, Tamagawa Seisakusho Model TM-VSM-211483-HGC). The horizontal axis is the applied magnetic field, and the vertical axis is the magnetization. Referring to FIG. 13, the magnetization curve shows a nearly rectangular hysteresis when the applied magnetic field is near 0 T. This indicates that the magnetization of the magnetization free layer of Example 5 is perpendicular to the film surface, and the magnetization is reversed.

[0072] [Magnetic memory] The magnetic memory according to the embodiment has the same configuration as the magnetic elements 10, 20, 40, 50 according to the above-mentioned embodiment, that is, the magnetic elements 10, 20, 40, 50 shown in FIG. 1, FIG. 3, FIG. 4A, and FIG. 4B. That is, the magnetic elements 10, 20, 40, 50 can be used as magnetic memories, and are referred to as the magnetic memories 10, 20, 40, 50, respectively. Referring to FIG. 1 and FIG. 3, the magnetic memory according to the embodiment uses the magnetization free layer 14 of the magnetic elements 10, 20, 40, 50 shown in FIG. 1, FIG. 3, FIG. 4A, and FIG. 4B as a recording layer. When writing information, the magnetic memories 10, 20, 40, 50 pass a pulse current between the terminals 11a and 11b connected to the wiring layer 11, so that a spin current flows in the stack 12 and acts on the magnetization of the magnetization free layer 14, and the magnetization direction of the magnetization free layer 14 is reversed according to the polarity and magnetization direction of the spin current. This changes the magnetic resistance between the terminal 13a connected to the electrode cap layer 13 and the terminal 11a or 11b, thereby recording information. The magnetic memories 10, 20, 40, 50 have the same effects as the above-mentioned magnetic elements 10, 20, 40, 50. The magnetic memories 10, 20, 40, 50 are manufactured in the same manner as the magnetic element shown in FIG. 5 and its description.

[0073] As examples of the magnetic memory, examples 6 and 7 were formed. <Example 6> In Example 6, a W wiring layer 11 was formed on a substrate by sputtering. 67.9 (Ta 82 B 18 ) 32.1 film (thickness 8 nm), and Co as the magnetization free layer 14 15 Fe 60 B 25 film (thickness 1.8 nm), MgO film (thickness 1.0 to 1.8 nm) as the tunnel barrier layer 15, a first ferromagnetic layer 31: Co-Fe-B film (thickness 2 nm) as the reference layer, a non-magnetic spacer layer 32: W film (thickness 0.15 nm), a second ferromagnetic layer 33: Co 70 Fe 30 (Thickness 0.15nm) / Ru(Thickness 0.15nm) / Co 70 Fe 30 (2.2 nm thick) laminate, and Ir as antiferromagnetic layer 3420 Mn 80 A layer (thickness 7 nm) was formed as a W film, and a laminate of Ru (thickness 3 nm) / Ta (thickness 1 nm) / Ru (thickness 1.5 nm) / Pt (thickness 2 nm) was formed as an electrode cap layer 13 in this order. 67.9 (Ta 82 B 18 ) 32.1 The film is made of W and Ta. 80 B 20 The composition ratio (67.9:32.1) was controlled by the sputtering power of each sputtering target.

[0074] <Example 7> In Example 7, a W wiring layer 11 was formed on a substrate by sputtering. 67.9 (Ta 82 B 18 ) 32.1 film (thickness 8 nm), and Co as the magnetization free layer 14 15 Fe 60 B 25 film (thickness 1.8 nm), MgO film (thickness 1.0 to 1.8 nm) as tunnel barrier layer 15, first ferromagnetic layer 31: Co-Fe-B film (thickness 2 nm) / non-magnetic spacer layer 32: W film (thickness 0.15 nm) / second ferromagnetic layer 33: Co 70 Fe 30 A layer (thickness 0.15 nm) was formed as a W film, and a laminate of Ru (thickness 1.5 nm) / Ta (thickness 4 nm) / Ru (thickness 1.5 nm) / Pt (thickness 2 nm) was formed as an electrode cap layer 13 in this order. 76 (Ta 80 B 20 ) 24 The film is made of W and Ta. 80 B 20 The composition ratio (76:24) was controlled by the sputtering power of each sputtering target.

[0075] Fig. 14 is a cross-sectional transmission electron microscope image of Example 6 relating to a magnetic memory. Fig. 14(a) is a cross-sectional transmission electron microscope image of the entirety of Example 6, and Fig. 14(b) is a cross-sectional transmission electron microscope image of the wiring layer of Example 6. Referring to Fig. 14(a), it can be seen that the reference layer has a crystalline structure with crystal planes appearing. On the other hand, referring to Fig. 14(b), it can be seen that the wiring layer has an amorphous structure with atoms arranged randomly.

[0076] 15 shows magnetoresistance curves of Example 6. FIG. 15(a) shows the magnetoresistance value R of the magnetic tunnel junction when the applied magnetic field is swept in the in-plane direction of the magnetization free layer of Example 6. MTJ FIG. 15(b) shows the magnetoresistance curve of the magnetic tunnel junction when the magnitude of the pulse current flowing through the wiring layer of Example 6 is changed. MTJ The pulse width of the pulse current was set to 100 μs.

[0077] 15(a), when the applied magnetic field is swept between −4 mT and 4 mT, the magnetoresistance curve of the magnetic tunnel junction of Example 6 changes from A to B to C to D to A. At B (2.6 mT) and D (−1.6 mT), the magnetization free layer 14 (Co 15 Fe 60 B 25 It can be seen that the magnetization direction of the free magnetization layer 14, i.e., the recording layer, is reversed, and the magnetoresistance value changes to a low resistance value (13.9 kΩ) and a high resistance value (33.0 kΩ), respectively. This shows that information can be recorded by the magnetization direction of the free magnetization layer 14, i.e., the recording layer. Referring to FIG. 15(b), when the current density of the pulse current applied to the wiring layer 11 of Example 6 is −4.8×10 6 A / cm 2 and 4.4×10 6 A / cm 2 When the magnetoresistance curve of the magnetic tunnel junction of Example 6 is changed between E→F→G→H→E, the magnetoresistance curve of the magnetic tunnel junction of Example 6 changes from E to F to G to H to E. 6 A / cm 2 ) and H(-2.7×10 6 A / cm 2 ), the magnetization free layer 14 (Co 15 Fe 60 B25 It can be seen that the magnetization direction of the free layer 14, i.e., the recording layer, is reversed, and the magnetoresistance values ​​change to a high resistance value (33.0 kΩ) and a low resistance value (13.9 kΩ), respectively. This shows that the magnetization of the free layer 14, i.e., the recording layer, can be reversed by applying a pulse current to the wiring layer 11, thereby recording information.

[0078] 16A and 16B are magnetoresistance curves of the magnetic memory according to the seventh embodiment. FIG. 16A shows the magnetoresistance value R of the magnetic tunnel junction when the applied magnetic field is swept in the in-plane direction of the magnetization free layer of the seventh embodiment. MTJ FIG. 16(b) shows the magnetoresistance curve of the magnetic tunnel junction when the magnitude of the pulse current flowing through the wiring layer of Example 7 is changed. MTJ The pulse width of the pulse current was set to 100 μs.

[0079] 16(a), when the applied magnetic field is swept between −4 mT and 4 mT, the magnetoresistance curve of the magnetic tunnel junction of Example 7 changes from A to B to C to D to A. At B (1.2 mT) and D (−1.5 mT), the magnetization free layer 14 (Co 15 Fe 60 B 25 It can be seen that the magnetization direction of the free magnetization layer 14, i.e., the recording layer, is reversed, and the magnetoresistance value changes to a low resistance value (6.1 kΩ) and a high resistance value (14.1 kΩ), respectively. This shows that information can be recorded by the magnetization direction of the free magnetization layer 14, i.e., the recording layer. Referring to FIG. 16(b), when the current density of the pulse current applied to the wiring layer 11 of Example 7 is −8×10 6 A / cm 2 and 8×10 6 A / cm 2 When the magnetoresistance curve of the magnetic tunnel junction of Example 7 is changed between E, F, G, H, and E, F(4.7×10 6 A / cm 2 ) and H(-4.3×10 6 A / cm 2 ), the magnetization free layer 14 (Co 15 Fe 60 B 25It can be seen that the magnetization direction of the free layer 14, i.e., the recording layer, is reversed and the magnetoresistance value changes to a high resistance value (14.1 kΩ) and a low resistance value (6.1 kΩ), respectively. This shows that the magnetization of the free layer 14, i.e., the recording layer, can be reversed by applying a pulse current to the wiring layer 11, thereby recording information.

[0080] 17 is a diagram for determining the characteristic values ​​of Examples 6 and 7. The horizontal axis of FIG. 17 represents the pulse width τ of the pulse current applied to the wiring layer. p divided by the reciprocal of the attempt frequency 1GHz, τ0 (τ p / τ0). τ0 is set to 1 ns. The vertical axis represents the magnetization free layer 14 (Co 15 Fe 60 B 25 The reversal current density j is the density of the pulse current when the magnetization of the film is reversed. SW In the figure, the triangle marks (△, ▲) represent Example 6, and the circle marks (◯, ●) represent Example 7. The reverse current density j SW is, and (τ p / τ0) can be described by the following equation:

number

[0081] FIG. 18 is a diagram showing characteristic values ​​of Example 6 and Example 7. Referring to FIG. 18, Example 6 and Example 7 have j c0is comparable to that of Non-Patent Document 5 and Non-Patent Document 6, in which the wiring layer is made of β-W. The thermal stability index is higher than that of Non-Patent Document 5 and Non-Patent Document 6. Furthermore, the heat treatment temperatures are 360°C and 400°C, respectively, which are more than 100°C higher than that of Non-Patent Document 5 and Non-Patent Document 6. This shows that Example 6 and Example 7 have extremely excellent heat resistance in the semiconductor manufacturing process.

[0082] <Example 8> Example 8 of the magnetic memory is an example in which the magnetization of the magnetization free layer is perpendicular to the film surface. It was shown by measuring the anomalous Hall effect that the magnetization of the magnetization free layer, which is perpendicular to the film surface, is reversed by the spin current of the pulse current applied to the wiring layer.

[0083] In Example 8, a W wiring layer 11 was formed on a substrate by sputtering. 67.9 (Ta 82 B 18 ) 32.1 The film (thickness 8 nm) and the free magnetic layer 14 are Fe 80 B 20 A laminate of a Ta (thickness 3 nm) / Ru (thickness 3 nm) film was formed in this order as the tunnel barrier layer 15, a MgO film (thickness 1.0 to 1.2 nm) as the tunnel barrier layer 15, and an electrode cap layer 13 as the Ta (thickness 3 nm) / Ru (thickness 3 nm). In Example 8, even if the reference layer is omitted, the phenomenon of the magnetization free layer being reversed is possible by measuring the anomalous Hall effect. However, the reference layer is essential for a magnetic memory. In measuring the anomalous Hall effect, the in-plane direction of the magnetization free layer, the direction in which the wiring layer 11 extends, is the x-direction, the direction perpendicular to the x-direction in the same plane is the y-direction, and the direction perpendicular to the film surface of the magnetization free layer is the z-direction. The Hall coefficient was obtained by measuring the voltage in the y-direction.

[0084] FIG. 19 is a diagram showing the anomalous Hall effect of the eighth embodiment of the magnetic memory. FIG. 19(a) shows the magnetic moment m / S (mA) per unit area for the magnitude μ0H of the applied magnetic field when the magnetic field (Hx) is swept in the in-plane direction (x direction) of the magnetization free layer (dashed line) and when the magnetic field (Hz) is swept in the direction perpendicular to the film surface of the magnetization free layer (z direction) (solid line). Referring to FIG. 18(a), when the magnetic field (Hx) is swept in the in-plane direction (x direction) of the magnetization free layer (dashed line), the curve shows the magnetic field applied to the hard axis of magnetization, and when the magnetic field (Hz) is swept in the direction perpendicular to the film surface of the magnetization free layer (z direction), the curve shows the magnetic field applied to the easy axis of magnetization. This shows that the magnetization of the magnetization free layer is perpendicular to the film surface.

[0085] Figure 19(b) shows the Hall coefficient curve when the applied magnetic field (Hz) is swept in the direction perpendicular to the film surface of the magnetization free layer (z direction). Referring to Figure 19(b), when a magnetic field is applied and swept in the direction perpendicular to the film surface of the magnetization free layer, a hysteresis curve with a high Hall coefficient and a low Hall coefficient is obtained. This shows that the magnetization of the magnetization free layer is perpendicular to the film surface, and the direction is reversed by the application of a magnetic field.

[0086] FIG. 19(c) shows Hall coefficient curves measured by changing the magnitude of the pulse current applied to the wiring layer of Example 8, where a bias magnetic field of 10 mT is applied in the in-plane direction (x direction) of the film surface of the magnetization free layer. Application of the bias magnetic field causes the magnetization of the magnetization free layer to tilt from the z direction to the x direction in the xz plane. Referring to FIG. 19(c), when the current density of the pulse current applied to the wiring layer 11 of Example 8 is changed to -1.7×10 11 A / cm 2 and 1.7×10 11 A / cm 2 When the Hall coefficient curve of the magnetic memory of Example 8 is changed between A → B → C → D → A. 11 A / cm 2 ) and D(-0.97×10 11 A / cm 2), the magnetization direction of the magnetization free layer is reversed, and the Hall coefficients change to 0.30Ω and -0.30Ω, respectively. This shows that the magnetization of the magnetization free layer, i.e., the recording layer, can be reversed by applying a pulse current to the wiring layer 11, and information can be recorded.

[0087] FIG. 19(d) shows the Hall coefficient curves measured by changing the magnitude of the pulse current applied to the wiring layer of Example 8, where a bias magnetic field of 10 mT is applied in the in-plane direction (-x direction) of the film surface of the magnetization free layer. Application of the bias magnetic field tilts the magnetization of the magnetization free layer from the z direction to the -x direction in the xz plane. Referring to FIG. 19(d), when the current density of the pulse current applied to the wiring layer of Example 8 is changed to -1.7×10 11 A / cm 2 and 1.7×10 11 A / cm 2 When the magnetic field is changed between F(1.25×10 and F(1.25×10), the Hall coefficient curve of the magnetic memory of Example 8 changes from E to F to G to H to E. 11 A / cm 2 ) and H(-1.17×10 11 A / cm 2 ), the magnetization direction of the magnetization free layer is reversed, and the Hall coefficients change to -0.30Ω and 0.30Ω, respectively. This shows that the magnetization of the magnetization free layer, i.e., the recording layer, can be reversed by applying a pulse current to the wiring layer 11, and information can be recorded.

[0088] [High frequency oscillator] FIG. 20 is a schematic diagram of a high-frequency oscillator according to an embodiment. Referring to FIG. 20, a high-frequency oscillator 60 according to an embodiment is formed by laminating a wiring layer 11, a magnetization free layer 14, a tunnel barrier layer 15, a reference layer 66, and an electrode cap layer 13 on the wiring layer 11. The reference layer 66 is formed by laminating a first ferromagnetic layer 31, a nonmagnetic spacer layer 32, and a second ferromagnetic layer 33 from the tunnel barrier layer 15 side. The high-frequency oscillator 60 has a configuration similar to that of the magnetic elements 10 and 20 according to the above-mentioned embodiment, that is, the magnetic elements 10 and 20 shown in FIG. 1 and FIG. 3. That is, the magnetic elements 10 and 20 can be used as the high-frequency oscillator 60. The high-frequency oscillator 4 is configured such that a current I flows between a terminal 11a and a terminal 11b connected to the wiring layer 11. SHE When current is applied to the wiring layer 11, the magnetization of the magnetization free layer 14 is subjected to a torque due to magnetic damping generated during precession and a spin orbit torque due to a spin current generated by the current applied to the wiring layer 11, so that the magnetization of the magnetization free layer 14 self-oscillates. As a result, the high-frequency oscillator 60 oscillates the voltage between the terminal 13a and the terminal 11a or the terminal 11b, and the oscillation signal V OSC The high-frequency oscillator 60 is manufactured in a manner similar to that of the magnetic element shown in FIG.

[0089] <Example 9> The high-frequency oscillator of Example 9 was formed under the same film configuration and forming conditions as those of the magnetic memory of Example 1. A direct current of −0.8 mA was applied to the wiring layer 11 to generate an oscillation signal V OSC was measured. FIG. 21 shows the oscillation signal V OSC The horizontal axis is the frequency, and the vertical axis is the oscillation signal V OSC 21, the power spectrum density of the oscillation signal V OSC It can be seen that the main wavelength component is 1.26 GHz.

[0090] Although the preferred embodiments of the present invention have been described in detail above, the present invention is not limited to such specific embodiments, and various modifications and variations are possible within the scope of the present invention described in the claims. [Explanation of symbols]

[0091] 10,20,40,50 Magnetic elements, magnetic memories 11 Wiring layer 12,22 Laminate 14 Magnetization free layer 15 Tunnel Barrier Layer 16,26,66 Reference layer 41 Thin Film 60 High Frequency Oscillator

Claims

1. a wiring layer having an amorphous structure containing tungsten and an additive element X; a stack having a magnetic tunnel junction on the wiring layer.

2. 2. The magnetic element according to claim 1, wherein the content of said additional element X in said wiring layer is 5 at % or more and 50 at % or less.

3. The magnetic element according to claim 1 , wherein the additional element X includes at least one element NM selected from the group consisting of B, P and C.

4. 4. The magnetic element according to claim 3, wherein the content of said element NM in said wiring layer is 5 at % or more and 50 at % or less.

5. 2. The magnetic element according to claim 1, wherein the additional element X includes at least one metal element M selected from the group consisting of Ta and Mo, and at least one element NM selected from the group consisting of B, P, and C.

6. 6. The magnetic element according to claim 5, wherein the content of the element NM in the additional element X in the wiring layer is 10 at % or more and 50 at % or less.

7. The stack having the magnetic tunnel junction includes a magnetic free layer, 2. The magnetic element according to claim 1, wherein the direction of magnetization of the magnetization free layer is parallel or perpendicular to the film surface of the magnetization free layer when no magnetic field is applied from outside the magnetic element.

8. 8. The magnetic element according to claim 7, wherein the magnetization free layer is formed directly on the wiring layer or via a thin film containing a material other than the wiring layer.

9. 9. The magnetic element according to claim 8, wherein the thin film contains at least one metal element or oxide of Ti, V, Cr, Co--O, Fe--O, Ni--O, Cu, Zr, Nb, Pd, Hf, Ir, Pt and Au.

10. A magnetic memory comprising the magnetic element according to any one of claims 1 to 9.

11. A high-frequency oscillator comprising the magnetic element according to any one of claims 1 to 9.

12. a step of forming a wiring layer having an amorphous structure, the step of forming the wiring layer using a material source including tungsten and an additive element X; forming a stack having a magnetic tunnel junction on the wiring layer; A method for manufacturing a magnetic element comprising the steps of:

13. The method for manufacturing a magnetic element according to claim 12 , wherein the additional element X includes at least one element NM selected from the group consisting of B, P and C.

14. 13. The method for manufacturing a magnetic element according to claim 12, wherein the additional element X includes at least one metal element M of Ta and Mo, and at least one element NM of B, P and C.

15. The method for manufacturing a magnetic element according to claim 12 , wherein in the step of forming the wiring layer, a first material source containing tungsten and a second material source containing the additional element X are used.

16. 16. The method for manufacturing a magnetic element according to claim 15, wherein in the step of forming the wiring layer, the wiring layer is formed by simultaneously or alternately releasing and depositing each of component elements from a first material source containing tungsten and a second material source containing the additive element X.

17. 17. The method for manufacturing a magnetic element according to claim 16, wherein in the step of forming the wiring layer, a first material source containing tungsten and a second material source containing the additive element X are alternately released and deposited to form a multilayer film structure in which a first layer containing tungsten and a second layer containing the additive element X are alternately stacked, and the film thickness of each of the first layer and the second layer is 1.0 nm or less.

18. 18. The method for manufacturing a magnetic element according to claim 17, wherein a thickness ratio of the thickness of the second layer to the sum of the thicknesses of the first layer and the second layer, i.e., thickness ratio = (thickness of the second layer) / {(thickness of the first layer) + (thickness of the second layer)}, is 0.10 or more and 0.50 or less.

19. A method for manufacturing a magnetic memory, comprising manufacturing a magnetic element according to any one of claims 12 to 18.

20. A method for producing a high frequency oscillator, comprising producing a magnetic element according to any one of claims 12 to 18.

Citation Information

Patent Citations

  • Spin-orbit torque switching element with tungsten nitride

    JP2021150639A

  • Spin-orbit torque MRAM and its fabrication

    JP2022507841A